Discovery of novel S1P2 antagonists. Part 2: Improving the profile of a series of 1, 3-bis(aryloxy)benzene derivatives. Issue 20 (15th October 2015) - Kusumi, Kensuke; Shinozaki, Koji; Yamaura, Yoshiyuki; Hashimoto, Ai; Kurata, Haruto; Naganawa, Atsushi; Ueda, Hideyuki; Otsuki, Kazuhiro; Matsushita, Takeshi; Sekiguchi, Tetsuya; Kakuuchi, Akito; Seko, Takuya
Graphical abstract: Abstract: Our initial lead compound2 was modified to improve its metabolic stability. The resulting compound5 showed excellent metabolic stability in rat and human liver microsomes. We subsequently designed and synthesized a hybrid compound of5 and the 1, 3-bis(aryloxy) benzene derivative1, which was previously reported by our group to be an S1P2 antagonist. This hybridization reaction gave compound9, which showed improved S1P2 antagonist activity and good metabolic stability. The subsequent introduction of a carboxylic acid moiety into9 resulted in14, which showed potent antagonist activity towards S1P2 with a much smaller species difference between human S1P2 and rat S1P2 . Compound14 also showed good metabolic stability and an improved safety profile compared with compound9 .